HUBUNGAN ANTARA TEMUAN AUDIT DAN BELANJA MODAL DENGAN PENDAPATAN ASLI DAERAH SEBAGAI VARIABEL INTERVENING - Kunthi Kusumaningtyas (AKT 15 UMY 134, 2015)
*134 Local government’s role as public services’ provider and institution to achieve greater national development purposes demand a monitoring system, evaluation, and systematic work gauging done to measure local government’s development. This study aims to determine the relation between audit finding and the capital expenditure using local government original revenue as an intervening variable . The population in this study is districts / cities in Indonesia. In this study, samples of 289 districts / cities were selected using purposive sampling method. The data used were secondary data, LGFR 2012. Analyzer used in this research was multiple regression and path analysis with SPSS. The result of this study states that audit finding has significant negative relation with local government original revenue, local government original revenue has significant negative relation with capital expenditure, and the audit finding doesn’t has relation with capital expenditure. The result of path analysis shows that audit finding has relation with capital expenditure using local government original revenue as an intervening variable